Improved Recognition of Hematogones From Precursor B-Lymphoblastic Leukemia by a Single Tube Flow Cytometric Analysis. Issue 6 (18th February 2020) - Don, Michelle D; Lim, Washington; Lo, Amanda; Cox, Brian; Huang, Qin; Kitahara, Sumire; Lopategui, Jean; Alkan, Serhan
Abstract: Objectives: To improve diagnostic accuracy in differentiating hematogones from leukemic blasts in cases of precursor B-lymphoblastic leukemia/lymphoma (B-ALL), particularly those that are posttreatment or after bone marrow transplant, and to provide an algorithmic approach to this diagnostic challenge. Methods: A seven-color antibody panel including CD10, CD19, CD45, CD38, CD34, CD58, and CD81 was generated to assess the feasibility of a single tube panel and provide an algorithmic approach to distinguish hematogones from B-ALL. Fifty-three cases were analyzed, and results were correlated with histology and ancillary studies. Results: There was a significant difference in mean fluorescent intensity (MFI) for CD81 and CD58 when comparing hematogones and B-ALL populations ( P < .001). B-ALL cases had a mean (SD) MFI of 24.6 (27.5; range, 2-125) for CD81 and 135.6 (72.6; range, 48-328) for CD58. Hematogones cases had a mean (SD) MFI of 70.2 (19.2; range, 42-123) for CD81 and 38.8 (9.4; range, 23-58) for CD58. Conclusions: The flow cytometry panel with the above markers and utilization of the proposed algorithmic approach provide differentiation of hematogones from B-ALL. This includes rare cases of hematogones and B-ALL overlap where additional ancillary studies are necessary. Abstract : 1. In cases of B-lymphoblastic leukemia (B-ALL), particularly those posttreatment or after bone marrow transplant, differentiating hematogones from leukemic blasts can be a diagnostic challenge. 2. A single multicolor flow cytometry tube including the markers for CD58 and CD81 can be used to distinguish hematogones from leukemic blasts in such cases. 3. This study provides a novel algorithmic approach using a single multicolor flow cytometry tube for distinguishing hematogones form leukemic blasts in everyday practice.